Persepsi Masyarakat terhadap Program Gerakan Nagari Gemar Membaca di Nagari Saok Laweh Kabupaten Solok - Iryana, Cholila Putri Tri; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractIn this paper discusses about community perceptions of the nagari movement loves to read program in Nagari Saok Laweh Solok district. This study aims to reveal: (1) community perceptions of the nagari movement loves to read program in Nagari Saok Laweh Solok district, (2) constraints found in nagari movement loves to read program. Data collected by quantitative research by spreading the questionnaire to the people of Nagari Saok laweh. The sample used was 145 (one hundred forty five) respondents. Data analysis conducted using quantitative method with descriptive method. The result of questionnaire was prepared by recapitulation of research result. The analysis by describing the results of recapitulation in a description to clarify the results of the numbers so easily understood. Based on the results of the study concluded as follows: (1) people's perception towards Nagari Movement program in Nagari Saok Laweh Kabupaten Solok from the indicators of understanding, responses and community appraisal give positive perception, (2) the constraints found in the Gariy Reading program can come from the community as well as from the program itself. Constraints from the community such as reading constraints, and still lack of public desire to read. Constraints from such programs, the lack of number of cadres in charge of causing books in some homes are not replaced.Â Keywords: Perseption, peoples, program